Modeling infiltration in irrigation project - Ali, Md. Hazrat; Lee, Teang Shui; Kwok, Chee Yan; Eloubaidy, Aziz F.; Foong, K. C. (Universiti Putra Malaysia, 1999)
The Richards equation does not yield analytical solutions for the flow field, except under restrictive choices of hydraulic properties relating to water content, hydraulic conductivity, and the soil matric potential (Govindaraju et al., 1996). This paper deals with the estimation of infiltration from Muda area by a widely used approximate theory-based infiltration model, known as the Green-Ampt model (1911). The variation of the suction head and hydraulic conductivity with moisture content studied by Brooks and Corey (1964) was applied in the present model. The infiltration rate for each month was estimated and the mean infiltration rate was found to be 1.04 mm/day, which is approximately equal to the MADA’s used value of 1 mm/day, indicating the adequacy of the model. The hydraulic conductivity of the Muda soil ranges from 1 x 10-7 to 8 x 10-6 cm/s (Kitamura, 1990). The hydraulic conductivity of the soil was perturbed up to its limiting value with 1 x 10-6 cm/s increment and the variation of the infiltration rate with hydraulic conductivity was plotted. The results from the perturbation show that the mean infiltration rate is linear with the hydraulic conductivity.